2010
DOI: 10.1002/14651858.cd006517.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral regimens for patients with HIV who fail first-line antiretroviral therapy

Abstract: There is limited evidence to evaluate second-line therapies in patients with HIV who fail first-line treatment with a WHO-recommended regimen. One randomised trial in 136 patients and two observational studies (both of low quality) suggest no difference in virological suppression whether or not lamivudine is maintained in a second-line regimen. While outcomes of second-line regimens with boosted PIs are favourable in general, there are no studies comparing boosted PIs directly in populations starting second-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…11 This high OT viral suppression rate occurred despite 69% of patients (for whom genotype data were available) having a GSS of 1. This observation potentially points to the potency of PI monotherapy that has been demonstrated in other studies 17,21,22 or possibly retained activity of TDF despite multiple thymidine analogue mutations (TAMs).…”
Section: Discussionmentioning
confidence: 56%
“…11 This high OT viral suppression rate occurred despite 69% of patients (for whom genotype data were available) having a GSS of 1. This observation potentially points to the potency of PI monotherapy that has been demonstrated in other studies 17,21,22 or possibly retained activity of TDF despite multiple thymidine analogue mutations (TAMs).…”
Section: Discussionmentioning
confidence: 56%
“…Drug combination using highly active antiretroviral therapy (HAART) has improved the survival of PLWHA [ 13 , 14 ]. There is evidence that Truvada (or tenofovir-containing regimens) may be superior to Combivir, in terms of fewer adverse effect, improved hemoglobin, and easier dosing [ 14 ]. Mortality was almost twice more likely among patients on Truvada-based 1st line therapy compared with Combivir-based therapy (95% CI 1.05–3.36) (see Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review [17] showed that there is insufficient evidence to evaluate second-line therapies in patients with HIV infection who fail first-line treatment with nonnucleoside reverse transcriptase inhibitor (NNRTI) 1 N(t)RTI combinations. Individualized treatment decisions are recommended to be based on patient treatment history, appropriate agents for inclusion and HIV drug resistance testing.…”
Section: Discussionmentioning
confidence: 99%